2011
DOI: 10.1037/a0024660
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, alcohol use attitudes, and alcohol use in a national sample of adolescents.

Abstract: The purpose of this study was to investigate alcohol use attitudes as a mediator of the relationship between religiosity and the frequency of past month alcohol use in a national sample of adolescents. Data were drawn from 18,314 adolescents who participated in the 2006 and 2007 National Survey on Drug Use and Health. Variables included religiosity, alcohol use attitudes, and past month frequency of alcohol use. Structural equation modeling was used to test alcohol use attitudes as a mediator of the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Religiosity has a strong influence on abstention from alcohol use, although abstention rates vary considerably in relation to the degree that individuals perceive their religion as discouraging of alcohol consumption (Michalak et al, 2007). Research findings suggesting that religiosity is generally protective against alcohol problems are consistent across national population-based studies in the United States, including studies based on data from the National Alcohol Survey (Michalak et al, 2007), the National Survey on Drug Use and Health (Edlund et al, 2010; Vaughan et al, 2011), and the General Social Survey (Allen and Lo, 2010). …”
Section: Introductionmentioning
confidence: 79%
“…Religiosity has a strong influence on abstention from alcohol use, although abstention rates vary considerably in relation to the degree that individuals perceive their religion as discouraging of alcohol consumption (Michalak et al, 2007). Research findings suggesting that religiosity is generally protective against alcohol problems are consistent across national population-based studies in the United States, including studies based on data from the National Alcohol Survey (Michalak et al, 2007), the National Survey on Drug Use and Health (Edlund et al, 2010; Vaughan et al, 2011), and the General Social Survey (Allen and Lo, 2010). …”
Section: Introductionmentioning
confidence: 79%
“…While religiosity in general has been found to be protective against substance use among adolescents, the protection provided by specific dimensions of religiosity and proximity to religious institutions among urban adolescents has not been extensively examined (Marsiglia et al, 2012; Vaughan, de Dios, Steinfeldt, & Kratz, 2011). At a descriptive level, the current findings showed that alcohol use is twice as prevalent as tobacco use among urban adolescents, and that 1 in 5 adolescents use marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…1–8 Although several factors may contribute to this protective effect—such as access to social support, 910 and shared values and beliefs 1112 —spirituality may play a role in SUD recovery that is distinct from the measured impact of social developmental factors, such as family make-up, gender, and age. 13 …”
Section: Introductionmentioning
confidence: 99%